Ransomware - Kidnapping personal data for ransom and the information as hostage - Ferreira, Márcio Ricardo; Kawakami, Cynthia (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
The mankind faces a new overview to legally handle with the hyper-connected society, in which personal data and privacy are closely related. This globalization affected directly the criminality, both in its extension and in its structure and occurrence, entailing the occurrence of new criminal conduct, such as the ransomware. The problem is that, the few existent legislations do not successfully encompass the kidnap of personal data for ransom. In this regard, this paper proposes an analysis on the vulnerability of personal data in the New Information Technologies and the Communication, the scope is to analyze the conduct and propose new solutions, aiming to bring more legal certainty to this issue. This new criminological reality deserves reflection, therefore, the present paper will adopt the comparative-deductive method to examine what the existent doctrine and jurisprudence state, in order to assess the necessity (or not) of the creation of a specific criminal legislation for privacy and personal data security of the Internet’s user. The main result found is the necessity of the creation of an autonomous field of Criminal Cyber Law to handle with the offensive conducts against information and the legislative evolution demanded to offer specific solutions to RANSOMWARE, which is a new conduct, extremely different from the extortion and kidnapping that society is used to, typical in this new reality where the Information Society lives.